A PVC / polyester composite material for high-performance hose and preparation method thereof
By using PVC/polyester composite materials and composite modifiers in PVC hoses, the aging problem of existing PVC hoses under high temperature and light is solved, which significantly improves the heat resistance, light resistance and toughness of the material, extends the service life and expands the application range.
Patent Information
- Application Number
- CN202411897072.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-23
AI Technical Summary
The existing PVC hoses have insufficient thermal aging performance, poor photoaging performance and insufficient toughness in high temperature environments, resulting in short service life and limited application range.
Using PVC/polyester composite material, the compatibility and interface bonding of the material are improved by adding polystyrene resin, polyester plasticizer and composite modifier, and the compatibility of the material is enhanced, and the heat resistance, weather resistance and mechanical strength are enhanced. The composite modifier constructs an organic-inorganic hybrid layer through surface modification and grafting reaction, improving the material's light resistance and thermal aging resistance.
It significantly improves the heat aging resistance, photoaging and toughness of PVC hoses, extends service life and expands the application range.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of PVC materials, and in particular to a PVC / polyester composite material for a high-performance hose and a preparation method thereof. Background Art
[0002] Hoses are key components in fluid delivery systems and are widely used in industrial production, agricultural irrigation, construction engineering, and daily life. Depending on the application environment, hoses need to meet a series of performance requirements, including mechanical properties, physical properties, chemical properties, and environmental adaptability. An ideal hose should have sufficient tensile and compressive strength, good wear resistance and toughness, excellent chemical corrosion resistance, and appropriate flexibility and sealing. At the same time, in actual use, the hose also needs to have good weather resistance and aging resistance to ensure a long service life.
[0003] As one of the five major general-purpose plastics, PVC (polyvinyl chloride) occupies an important position in the global plastic production. PVC material has the characteristics of moderate density, good mechanical strength, excellent chemical corrosion resistance, etc. Its unique molecular structure gives the material excellent flame retardant properties, and the oxygen index can reach 45~50. In terms of chemical properties, PVC exhibits excellent acid and alkali resistance and oil resistance, and has good air tightness and water tightness. In addition, PVC also has the characteristics of moderate processing temperature range and easy composite modification. It can be formed by various processing methods such as extrusion and injection molding. Due to the rich source of raw materials and mature production technology, PVC materials have a high cost-effectiveness and are widely used in various plastic products.
[0004] PVC hose is an important application form of PVC materials in the field of fluid transportation. According to the structural characteristics, it can be divided into single-layer PVC hose, fiber-reinforced PVC hose and multi-layer composite PVC hose. Single-layer PVC hose has a simple structure and is mainly used in low-pressure transportation occasions; fiber-reinforced PVC hose increases the strength by adding fiber materials to the PVC matrix, and is suitable for medium-pressure transportation occasions; multi-layer composite PVC hose adopts a three-layer structure of inner and outer layers of PVC and a middle layer of reinforcement material, has excellent pressure resistance, and is widely used in high-pressure transportation occasions.
[0005] In practical applications, the performance of PVC hoses is mainly affected by factors such as material formulation, process conditions and structural design. Material formulation includes the selection of PVC resin, the type and amount of plasticizer, the design of the stabilizer system, and the nature and content of fillers; process conditions involve the control of the mixing process, the optimization of extrusion molding parameters, and the selection of cooling and shaping methods; structural design needs to consider aspects such as wall thickness distribution, reinforcement layer design and interface bonding. The reasonable configuration of these factors has an important influence on ensuring the comprehensive performance of PVC hoses.
[0006] CN115674792A discloses a PVC hose and its preparation method and application, which comprises an inner rubber layer, a fiber layer and an outer rubber layer from the inside to the outside; the raw materials for preparing the inner rubber layer include elastomer, adipic acid polyester, guanidine salt oligomer, polyvinyl chloride and peroxide; the raw materials for preparing the outer rubber layer include elastomer, polyvinyl chloride and adipic acid polyester; the elastomer includes at least one of powdered nitrile and ethylene-vinyl acetate-carbon monoxide terpolymer.
[0007] However, with the development of industrial technology and the increase in application demand, existing PVC hoses have exposed some problems that need to be solved in actual use. The first is insufficient thermal aging performance. Under long-term high temperature environment, the material is prone to thermal oxidation degradation, resulting in a decrease in mechanical properties, cracking and discoloration on the surface, which seriously affects the service life. Secondly, the problem of light aging is prominent. Under ultraviolet light, the material undergoes photooxidative degradation, causing molecular chain breakage, resulting in surface powdering and fading, which limits the outdoor service life of the product. In addition, the toughness of existing PVC hoses is generally insufficient, manifested as obvious low-temperature brittleness and poor impact resistance, and is prone to cracking under repeated bending and fatigue loads.
[0008] Therefore, developing a PVC / polyester composite material with excellent heat aging resistance, light aging resistance and good toughness is of great practical significance for improving the service life and application scope of PVC hoses. Summary of the invention
[0009] In order to solve the deficiencies in the prior art, the purpose of the present invention is to provide a PVC / polyester composite material for a high-performance hose and a preparation method thereof. The addition of a composite modifier significantly improves the compatibility of PVC with other components, enhances the interfacial bonding force, and enables the final material to have excellent heat resistance, weather resistance and mechanical strength.
[0010] In order to achieve the above object, the present invention adopts the following technical solution:
[0011] A PVC / polyester composite material for a high-performance hose is prepared from the following components, measured by weight: 60-70 parts of PVC resin, 15-30 parts of polystyrene resin, 10-30 parts of filler, 5-15 parts of polyester plasticizer, 8-16 parts of composite modifier, 0.5-2 parts of lubricant, 1-2 parts of heat stabilizer, and 0-1.5 parts of colorant.
[0012] Preferably, the preparation method of the composite modifier comprises the following steps:
[0013] (1) adding KH580 to an ethanol / water solution, then adding nano-titanium dioxide, ultrasonically treating, adjusting the pH with glacial acetic acid, reflux stirring, centrifuging, washing, and drying the product to obtain pretreated titanium dioxide;
[0014] Surface modification of silane coupling agent: KH580 is hydrolyzed in an aqueous ethanol solution to generate a silanol-based active intermediate, which undergoes a condensation reaction with the hydroxyl groups on the surface of titanium dioxide to form a Si-O-Ti covalent bond, achieving initial surface modification. This step lays the foundation for subsequent modification and constructs a stable organic-inorganic hybrid layer on the surface of titanium dioxide.
[0015] Preferably, in step (1), the volume ratio of anhydrous ethanol to deionized water in the ethanol / water solution is 8-12:1; and the dosage ratio of KH580, ethanol / water solution, and nano-titanium dioxide is 4-10 mL: 80-130 mL: 10 g.
[0016] Preferably, in step (1), the ultrasonic treatment time is 15-40 min; the pH is adjusted to 4.0-5.5; and the reflux stirring conditions are reflux stirring at 60-70° C. for 3-5 h.
[0017] (2) dispersing the pretreated titanium dioxide in a dichloromethane / n-hexane mixed solvent, then adding 3-amino-2-butenethioamide and benzoin dimethyl ether, continuously introducing nitrogen, reacting under ultraviolet light, centrifuging, washing, and drying the product to obtain thioamidated titanium dioxide;
[0018] Photoinitiated grafting to introduce thioamide groups: Under an inert atmosphere, benzoin dimethyl ether generates free radicals under ultraviolet light, initiating the grafting reaction of 3-amino-2-butenethioamide on the surface of pretreated titanium dioxide. Through the free radical initiation mechanism, a modified layer containing thioamide groups is formed on the surface, providing reaction sites for the subsequent introduction of long-chain molecules.
[0019] Preferably, in step (2), the volume ratio of dichloromethane to n-hexane in the dichloromethane / n-hexane mixed solvent is 2.8-3.2:1; the amount ratio of pretreated titanium dioxide, dichloromethane / n-hexane mixed solvent, 3-amino-2-butenethioamide, and benzoin dimethyl ether is 10 g: 70-100 mL: 3-7 g: 0.08-0.3 g.
[0020] Preferably, in step (2), the reaction conditions are irradiation with 12-25W, 365nm ultraviolet light for 2-3h in a water bath at 22-28°C; and the product is washed with dichloromethane and anhydrous ethanol for 2-4 times.
[0021] (3) Myristic acid, EDC and NHS are added to a dichloromethane / carbon tetrachloride mixed solvent for activation to obtain an activation solution; thioamidated titanium dioxide is dispersed in the dichloromethane / carbon tetrachloride mixed solvent and subjected to ultrasonic treatment, and then added to the activation solution, stirred for reaction, and the product is centrifuged, washed and dried to obtain the composite modifier.
[0022] Grafting long-chain fatty acids by amidation reaction: The EDC / NHS system activates the carboxyl group of myristic acid to generate an active ester intermediate, which then undergoes an amidation reaction with the amino group on the thioamide group on the titanium dioxide surface, ultimately constructing an organic modified layer with a long-chain structure on the titanium dioxide surface.
[0023] Preferably, in step (3), the volume ratio of dichloromethane to carbon tetrachloride in the dichloromethane / carbon tetrachloride mixed solvent is 1.8-2.2:1; the amount ratio of myristic acid, EDC, NHS, and dichloromethane / carbon tetrachloride mixed solvent is 2-4 g:1.5-3 g:0.6-1.5 g:70-100 mL; the amount ratio of thioamidated titanium dioxide to dichloromethane / carbon tetrachloride mixed solvent is 10 g:15-30 mL; the amount ratio of myristic acid to thioamidated titanium dioxide is 2-4 g:10 g.
[0024] Preferably, in step (3), the activation conditions are activation at 20-25°C for 1-2 hours; ultrasonic treatment for 10-20 minutes; stirring reaction conditions are stirring reaction at 20-25°C for 12-18 hours; and the product is washed with dichloromethane, anhydrous ethanol, and acetone for 2-4 times in sequence.
[0025] Preferably, the polyester plasticizer is one or more of PPA-1500, PPA-2000, PPA-2500, and PPA-6000; the filler is 0.02-1 μm calcium carbonate; the lubricant is calcium stearate; and the heat stabilizer is a calcium zinc stabilizer.
[0026] Preferably, the polymerization degree of PVC is 900-1500; the melt index of polystyrene resin is 4-10 g / 10 min; and the particle size of nano titanium dioxide is 100-300 nm.
[0027] The present invention also claims protection for a method for preparing the high-performance PVC / polyester composite material for a hose, comprising the following steps: uniformly mixing the raw materials according to a ratio in a high-speed mixer to obtain a mixture, then adding the mixture to an internal mixer and internally kneading at 150-160° C. for 20-40 minutes to obtain a clinker, feeding the clinker into a twin-screw extruder at 165-175° C. for extrusion granulation, hot pelletizing, fan cooling, and conveying to a silo to obtain the high-performance PVC / polyester composite material for a hose.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention provides a PVC / polyester composite material for high-performance hoses, wherein the synergistic effect of PVC resin and polystyrene resin improves the mechanical properties and processing properties of the material, the introduction of polyester plasticizers not only ensures the flexibility of the material but also reduces the risk of plasticizer precipitation, and the addition of fillers improves the rigidity and dimensional stability of the material. In particular, the addition of composite modifiers significantly improves the compatibility of PVC with other components, enhances the interface bonding force, and makes the final material have excellent heat resistance, weather resistance and mechanical strength.
[0030] 2. The present invention provides a method for preparing a composite modifier, firstly, surface modification of nano titanium dioxide is performed by using a silane coupling agent KH580; then, thioamide groups are introduced on the surface by a photoinitiated grafting method; and finally, long-chain fatty acids are grafted onto the surface by an amidation reaction. This step-by-step construction method can accurately control the progress of each step of the reaction, ensuring that the final product has good structural controllability.
[0031] 3. The present invention provides a composite modifier. First, nano-titanium dioxide as the core can effectively absorb and scatter ultraviolet light with its excellent ultraviolet shielding ability, prevent light energy from directly acting on the PVC molecular chain, inhibit the generation of free radicals during photooxidative degradation, and significantly improve the material's anti-light aging performance. The organic silicon layer formed on its surface by the silane coupling agent KH580 provides a stable chemical bonding interface, laying the foundation for the introduction of subsequent functional groups. Secondly, the introduced thioamide group has a dual role: on the one hand, it can combine with chlorine free radicals and polyvinyl chloride free radicals to form a stable macromolecular structure, effectively prevent the oxidation and dehydrochlorination process of polyvinyl chloride, and significantly improve the heat aging resistance; on the other hand, its amino group can absorb the hydrogen chloride produced by degradation, inhibit the autocatalytic effect, and stabilize the unstable chlorine atoms on the PVC molecular chain, further enhancing the thermal stability and crosslinking density of the material. The synergistic effect of nano-titanium dioxide and thioamide groups realizes all-round protection against photothermal aging: while titanium dioxide blocks external light radiation, the thioamide group can also capture various free radicals generated during photothermal aging, and jointly improve the service life of the material from both the source and process dimensions. Finally, the grafted long-chain fatty acid increases the free volume of the PVC / polyester material through the non-polar alkyl carbon chain, improves the flexibility of the composite material, and its long molecular chain can also form an effective entanglement with the PVC molecular chain, enhancing the interface bonding between the nano-titanium dioxide and the matrix, and can effectively absorb energy and prevent cracks when subjected to external forces. This layer-by-layer modified structure not only ensures the uniform distribution of the composite modifier in the PVC matrix, but also significantly improves the overall performance of the material through multiple action mechanisms. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. Of course, the specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.
[0033] Unless otherwise specified, the chemical reagents and materials in the present invention are purchased from commercial sources or synthesized from raw materials purchased from commercial sources.
[0034] Polystyrene was purchased from Formosa Polystyrene Co., Ltd., brand GPPS535N;
[0035] Nano-titanium dioxide is rutile titanium dioxide, purchased from Hangzhou Jiupeng New Materials Co., Ltd., model CY-T200, with a surface area of 5~15m 2 / g, particle size 200nm.
[0036] A method for preparing a PVC / polyester composite material for a high-performance hose comprises the following steps:
[0037] (1) Add 4-10 mL KH580 to 80-130 mL ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water is 8-12:1), then add 10 g nano-titanium dioxide, ultrasonically treat for 15-40 min, adjust the pH to 4.0-5.5 with glacial acetic acid, reflux and stir at 60-70 °C for 3-5 h, centrifuge the product, wash with anhydrous ethanol for 3-5 times, and dry to obtain pretreated titanium dioxide;
[0038] (2) Disperse 10 g of pretreated titanium dioxide in 70-100 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 2.8-3.2:1), then add 3-7 g of 3-amino-2-butenethioamide and 0.08-0.3 g of benzoin dimethyl ether, continuously introduce nitrogen, irradiate with 12-25 W, 365 nm ultraviolet light for 2-3 h in a water bath at 22-28 °C, centrifuge the product, wash with dichloromethane and anhydrous ethanol 2-4 times, and dry to obtain thioamidated titanium dioxide;
[0039] (3) Add 2-4 g myristic acid, 0.6-1.5 g EDC and 1.5-3 g NHS to 70-100 mL dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride is 1.8-2.2:1) and activate at 20-25°C for 1-2 h to obtain an activation solution; disperse 10 g thioamidated titanium dioxide in 15-30 mL dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride is 1.8-2.2:1) and ultrasonically treat for 10-20 min, then add it to the activation solution, stir and react at 20-25°C for 12-18 h, centrifuge the product, wash it with dichloromethane, anhydrous ethanol and acetone for 2-4 times, and dry it to obtain a composite modifier;
[0040] (4) 60-70 parts of PVC resin, 15-30 parts of polystyrene resin, 10-30 parts of calcium carbonate, 5-15 parts of polyester plasticizer PPA-2500, 8-16 parts of composite modifier, 0.5-2 parts of calcium stearate, 1-2 parts of calcium zinc stabilizer and 0-1.5 parts of colorant are uniformly mixed in a high-speed mixer to obtain a mixture, which is then added to an internal mixer and kneaded at 150-160° C. for 20-40 minutes to obtain a clinker, which is then put into a twin-screw extruder for extrusion and granulation at 165-175° C., and then hot pelletized, cooled by a fan and transported into a silo to obtain the PVC / polyester composite material for high-performance hoses.
[0041] The present invention will be further described below through specific embodiments.
[0042] Example 1
[0043] A method for preparing a PVC / polyester composite material for a high-performance hose comprises the following steps:
[0044] (1) 10 mL of KH580 was added to 130 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 12:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment for 40 min. The pH was adjusted to 5.5 with glacial acetic acid, and refluxed at 70 °C for 3 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0045] (2) Disperse 10 g of pretreated titanium dioxide in 100 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 3.2:1), then add 7 g of 3-amino-2-butenethioamide and 0.3 g of benzoin dimethyl ether, continue to introduce nitrogen, irradiate with 25 W, 365 nm ultraviolet light for 2 h in a 28 ° C water bath, centrifuge the product, wash it three times with dichloromethane and anhydrous ethanol in sequence, and dry it to obtain thioamidated titanium dioxide;
[0046] (3) 4 g of myristic acid, 1.5 g of EDC, and 3 g of NHS were added to 100 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2.2:1) and activated at 25°C for 1 h to obtain an activated solution; 10 g of thioamidated titanium dioxide was dispersed in 30 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2.2:1) and ultrasonically treated for 20 min, then added to the activated solution, stirred and reacted at 25°C for 12 h, the product was centrifuged and washed three times with dichloromethane, anhydrous ethanol, and acetone, and dried to obtain a composite modifier;
[0047] (4) 700 g of PVC1200 resin, 300 g of polystyrene resin, 300 g of calcium carbonate, 150 g of polyester plasticizer PPA-2500, 160 g of composite modifier, 20 g of calcium stearate, and 20 g of calcium zinc stabilizer were mixed uniformly in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker. The clinker was put into a twin-screw extruder for extrusion and granulation at 170° C., and then hot pelletized, cooled by a fan, and transported into a silo to obtain the PVC / polyester composite material for high-performance hoses.
[0048] Example 2
[0049] A method for preparing a PVC / polyester composite material for a high-performance hose comprises the following steps:
[0050] (1) 8 mL of KH580 was added to 120 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 10:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment was performed for 30 min. The pH was adjusted to 5.0 with glacial acetic acid, and the mixture was refluxed and stirred at 66 °C for 4 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0051] (2) Disperse 10 g of pretreated titanium dioxide in 90 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 3:1), then add 6 g of 3-amino-2-butenethioamide and 0.2 g of benzoin dimethyl ether, continue to introduce nitrogen, irradiate with 20 W, 365 nm ultraviolet light for 2.5 h in a 26 ° C water bath, centrifuge the product, wash it three times with dichloromethane and anhydrous ethanol in sequence, and dry it to obtain thioamidated titanium dioxide;
[0052] (3) 3 g of myristic acid, 1.2 g of EDC, and 2 g of NHS were added to 90 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2:1) and activated at 24°C for 1.5 h to obtain an activated solution; 10 g of thioamidated titanium dioxide was dispersed in 25 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2:1) and ultrasonically treated for 15 min, then added to the activated solution, stirred and reacted at 24°C for 14 h, the product was centrifuged and washed three times with dichloromethane, anhydrous ethanol, and acetone, and dried to obtain a composite modifier;
[0053] (4) 660 g of PVC1200 resin, 250 g of polystyrene resin, 250 g of calcium carbonate, 120 g of polyester plasticizer PPA-2500, 120 g of composite modifier, 15 g of calcium stearate and 15 g of calcium zinc stabilizer were mixed uniformly in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker. The clinker was put into a twin-screw extruder for extrusion and granulation at 170° C., and then hot pelletized, cooled by a fan and transported to a silo to obtain the PVC / polyester composite material for high-performance hoses.
[0054] Example 3
[0055] A method for preparing a PVC / polyester composite material for a high-performance hose comprises the following steps:
[0056] (1) 6 mL of KH580 was added to 100 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 10:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment for 20 min. The pH was adjusted to 4.5 with glacial acetic acid, and refluxed at 65 °C for 4 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0057] (2) Disperse 10 g of pretreated titanium dioxide in 80 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 3:1), then add 5 g of 3-amino-2-butenethioamide and 0.15 g of benzoin dimethyl ether, continue to introduce nitrogen, irradiate with 20 W, 365 nm ultraviolet light for 2.5 h in a 24 ° C water bath, centrifuge the product, wash it three times with dichloromethane and anhydrous ethanol in sequence, and dry it to obtain thioamidated titanium dioxide;
[0058] (3) 3 g of myristic acid, 1.0 g of EDC, and 2 g of NHS were added to 80 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2:1) and activated at 22°C for 1.5 h to obtain an activated solution; 10 g of thioamidated titanium dioxide was dispersed in 20 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 2:1) and ultrasonically treated for 15 min, then added to the activated solution, stirred and reacted at 22°C for 15 h, the product was centrifuged and washed three times with dichloromethane, anhydrous ethanol, and acetone, and dried to obtain a composite modifier;
[0059] (4) 620 g of PVC1200 resin, 200 g of polystyrene resin, 200 g of calcium carbonate, 100 g of polyester plasticizer PPA-2500, 100 g of composite modifier, 10 g of calcium stearate, and 14 g of calcium zinc stabilizer were mixed uniformly in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker. The clinker was put into a twin-screw extruder and extruded and granulated at 170° C., and then hot pelletized, cooled by a fan, and transported into a silo to obtain the high-performance PVC / polyester composite material for a hose.
[0060] Example 4
[0061] A method for preparing a PVC / polyester composite material for a high-performance hose comprises the following steps:
[0062] (1) 4 mL of KH580 was added to 80 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 8:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment was performed for 15 min. The pH was adjusted to 4.0 with glacial acetic acid, and the mixture was refluxed and stirred at 60 °C for 5 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0063] (2) Disperse 10 g of pretreated titanium dioxide in 70 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 2.8:1), then add 3 g of 3-amino-2-butenethioamide and 0.08 g of benzoin dimethyl ether, continue to introduce nitrogen, irradiate with 20 W, 365 nm ultraviolet light for 3 h in a 22 ° C water bath, centrifuge the product, wash it three times with dichloromethane and anhydrous ethanol in sequence, and dry it to obtain thioamidated titanium dioxide;
[0064] (3) 2 g of myristic acid, 0.6 g of EDC, and 1.5 g of NHS were added to 70 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 1.8:1) and activated at 20°C for 2 h to obtain an activation solution; 10 g of thioamidated titanium dioxide was dispersed in 15 mL of a dichloromethane / carbon tetrachloride mixed solvent (the volume ratio of dichloromethane to carbon tetrachloride was 1.8:1) and ultrasonically treated for 10 min, then added to the activation solution, stirred and reacted at 20°C for 18 h, the product was centrifuged and washed three times with dichloromethane, anhydrous ethanol, and acetone, and dried to obtain a composite modifier;
[0065] (4) 600 g of PVC1200 resin, 150 g of polystyrene resin, 100 g of calcium carbonate, 50 g of polyester plasticizer PPA-2500, 80 g of composite modifier, 5 g of calcium stearate, and 10 g of calcium zinc stabilizer were mixed uniformly in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker. The clinker was put into a twin-screw extruder for extrusion and granulation at 170° C., and then hot pelletized, cooled by a fan, and transported into a silo to obtain the PVC / polyester composite material for high-performance hoses.
[0066] Comparative Example 1
[0067] A method for preparing a PVC / polyester composite material for a hose comprises the following steps:
[0068] (1) 10 mL of KH580 was added to 130 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 12:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment for 40 min. The pH was adjusted to 5.5 with glacial acetic acid, and refluxed at 70 °C for 3 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0069] (2) Disperse 10 g of pretreated titanium dioxide in 100 mL of a dichloromethane / n-hexane mixed solvent (the volume ratio of dichloromethane to n-hexane is 3.2:1), then add 7 g of 3-amino-2-butenethioamide and 0.3 g of benzoin dimethyl ether, continue to introduce nitrogen, irradiate with 25 W, 365 nm ultraviolet light for 2 h in a 28 ° C water bath, centrifuge the product, wash it three times with dichloromethane and anhydrous ethanol in sequence, and dry it to obtain thioamidated titanium dioxide;
[0070] (3) 700 g of PVC1200 resin, 300 g of polystyrene resin, 300 g of calcium carbonate, 150 g of polyester plasticizer PPA-2500, 160 g of thioamidated titanium dioxide, 20 g of calcium stearate, and 20 g of calcium zinc stabilizer were mixed uniformly in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker. The clinker was put into a twin-screw extruder at 170° C. for extrusion granulation, hot pelletizing, fan cooling, and conveying to a silo to obtain the PVC / polyester composite material for the hose.
[0071] Comparative Example 2
[0072] A method for preparing a PVC / polyester composite material for a hose comprises the following steps:
[0073] (1) 10 mL of KH580 was added to 130 mL of ethanol / water solution (the volume ratio of anhydrous ethanol to deionized water was 12:1), followed by the addition of 10 g of nano-titanium dioxide, and ultrasonic treatment for 40 min. The pH was adjusted to 5.5 with glacial acetic acid, and refluxed at 70 °C for 3 h. The product was centrifuged, washed with anhydrous ethanol for 4 times, and dried to obtain pretreated titanium dioxide.
[0074] (2) 700 g of PVC1200 resin, 300 g of polystyrene resin, 300 g of calcium carbonate, 150 g of polyester plasticizer PPA-2500, 160 g of pretreated titanium dioxide, 20 g of calcium stearate, and 20 g of calcium zinc stabilizer are uniformly mixed in a high-speed mixer to obtain a mixture, which is then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker, which is then put into a twin-screw extruder for extrusion and granulation at 170° C., and then hot pelletized, cooled by a fan, and transported into a silo to obtain the PVC / polyester composite material for the hose.
[0075] Comparative Example 3
[0076] A method for preparing a PVC / polyester composite material for a hose comprises the following steps:
[0077] 700 g of PVC1200 resin, 300 g of polystyrene resin, 300 g of calcium carbonate, 150 g of polyester plasticizer PPA-2500, 20 g of calcium stearate and 20 g of calcium zinc stabilizer were uniformly mixed in a high-speed mixer to obtain a mixture, which was then added to an internal mixer and kneaded at 155° C. for 30 min to obtain a clinker, and the clinker was put into a twin-screw extruder for extrusion and granulation at 170° C., and hot pelletized, cooled by a fan and transported into a silo to obtain the PVC / polyester composite material for the hose.
[0078] The PVC / polyester composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were processed into test samples of 100 mm×100 mm×20 mm for performance testing; the tensile properties were tested at 25°C and 50 mm / min tensile rate using a universal testing machine with reference to GB / T 1040.3-2006 "Determination of tensile properties of plastics Part 3: Test conditions for films and sheets"; the impact properties were tested by punching a 2 mm notch in the sample with reference to GB / T1843-2008 "Determination of cantilever beam impact strength of plastics"; the samples were placed in hot air at 120°C for artificial accelerated aging for 250 hours, cooled to room temperature, and tested for tensile properties and impact properties again, and the tensile strength retention rate and impact strength retention rate were calculated to test the heat aging resistance; the samples were placed in a 50°C ultraviolet aging test box for ultraviolet accelerated aging for 20 hours, and the color difference change ΔE of the composite material before and after aging was tested using a colorimeter, ΔE=[(a-a1) 2 +(b-b1) 2 +(L-L1) 2 ] 1 / 2 , ΔE is the color difference value, L represents the brightness axis, a represents the yellow-green axis, and b represents the yellow-blue axis. See Table 1 for specific data.
[0079] Table 1 Performance test results of PVC / polyester composite materials
[0080]
[0081] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A PVC / polyester composite material for a high-performance hose, characterized in that: The composition is made of the following components by weight: 60-70 parts of PVC resin, 15-30 parts of polystyrene resin, 10-30 parts of filler, 5-15 parts of polyester plasticizer, 8-16 parts of composite modifier, 0.5-2 parts of lubricant, 1-2 parts of heat stabilizer, and 0-1.5 parts of colorant; The preparation method of the composite modifier comprises the following steps: (1) adding KH580 to an ethanol / water solution, then adding nano-titanium dioxide, ultrasonically treating, adjusting the pH with glacial acetic acid, reflux stirring, centrifuging, washing, and drying the product to obtain pretreated titanium dioxide; (2) dispersing the pretreated titanium dioxide in a dichloromethane / n-hexane mixed solvent, then adding 3-amino-2-butenethioamide and benzoin dimethyl ether, continuously introducing nitrogen, reacting under ultraviolet light, centrifuging, washing, and drying the product to obtain thioamidated titanium dioxide; (3) Myristic acid, EDC and NHS are added to a dichloromethane / carbon tetrachloride mixed solvent for activation to obtain an activation solution; thioamidated titanium dioxide is dispersed in the dichloromethane / carbon tetrachloride mixed solvent and subjected to ultrasonic treatment, and then added to the activation solution, stirred for reaction, and the product is centrifuged, washed and dried to obtain the composite modifier.
2. The high-performance PVC / polyester composite material for hose according to claim 1, characterized in that: In step (1), the volume ratio of anhydrous ethanol to deionized water in the ethanol / water solution is 8-12:1; the dosage ratio of KH580, ethanol / water solution, and nano-titanium dioxide is 4-10 mL: 80-130 mL: 10 g.
3. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: In step (1), the ultrasonic treatment time is 15-40 min; the pH is adjusted to 4.0-5.5; and the reflux stirring condition is reflux stirring at 60-70° C. for 3-5 h.
4. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: In step (2), the volume ratio of dichloromethane to n-hexane in the dichloromethane / n-hexane mixed solvent is 2.8-3.2:1; the amount ratio of pretreated titanium dioxide, dichloromethane / n-hexane mixed solvent, 3-amino-2-butenethioamide, and benzoin dimethyl ether is 10 g: 70-100 mL: 3-7 g: 0.08-0.3 g.
5. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: In step (2), the reaction conditions are irradiation with 12-25W, 365nm ultraviolet light for 2-3h in a water bath at 22-28°C; the product is washed with dichloromethane and anhydrous ethanol 2-4 times in sequence.
6. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: In step (3), the volume ratio of dichloromethane to carbon tetrachloride in the dichloromethane / carbon tetrachloride mixed solvent is 1.8-2.2:1; the amount ratio of myristic acid, EDC, NHS, and dichloromethane / carbon tetrachloride mixed solvent is 2-4 g:1.5-3 g:0.6-1.5 g:70-100 mL; the amount ratio of thioamidated titanium dioxide to dichloromethane / carbon tetrachloride mixed solvent is 10 g:15-30 mL; the amount ratio of myristic acid to thioamidated titanium dioxide is 2-4 g:10 g.
7. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: In step (3), the activation conditions are activation at 20-25° C. for 1-2 h; ultrasonic treatment for 10-20 min; stirring reaction conditions are stirring reaction at 20-25° C. for 12-18 h; and the product is washed with dichloromethane, anhydrous ethanol, and acetone 2-4 times in sequence.
8. The PVC / polyester composite material for high-performance hose according to claim 1, characterized in that: The polyester plasticizer is one or more of PPA-1500, PPA-2000, PPA-2500, and PPA-6000; the filler is 0.02-1 μm calcium carbonate; the lubricant is calcium stearate; and the heat stabilizer is a calcium zinc stabilizer.
9. A method for preparing a PVC / polyester composite material for a high-performance hose as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: uniformly mixing the raw materials according to a proportion in a high-speed mixer to obtain a mixture, then adding the mixture into an internal mixer and internally mixing at 150-160° C. for 20-40 minutes to obtain a clinker, feeding the clinker into a twin-screw extruder for extrusion and granulation at 165-175° C., hot pelletizing, fan cooling, and conveying into a silo to obtain the high-performance PVC / polyester composite material for a hose.
Citation Information
Patent Citations
Production method of conductive rubber sponge transfer roller, and sponge composite
CN102156399A
Adhesive, preparation method thereof, and application to insulation of electric machine winding
CN109401700A